Postgraduate student-supervisor interface: issues and challenges - Mohd Riji, Haliza; Syed Hassan, Syed Tajuddin; Ahmad, Shamsuddin (Universiti Putra Malaysia Press, 2013)
In this qualitative paper we discuss our face-to-face experience with 28 foreign (mainly from Iran) postgraduate students who registered with the Department of Community Health, Faculty of Medicine and Health Science and 31 who registered with the Department of Professional Development and Continuing Education, Faculty of Educational Studies, UPM. The paper addresses itself to three principal areas of concern: firstly, the supervisor-student relationship; secondly, the students’ literacy and academic competency; thirdly, academic and social cultural interface. The discussions are predicated on our personal experiences with these students over a three-year period. The influx of postgraduate students, particularly from Iran and Middle Eastern countries made it necessary for us to pay due attention to our encounters with them. The locus of tensions largely dwelt on UPM’s educational system and values. Academic incompetence, language and cultural differences are major issues. Understanding of related issues will benefit both the students and UPM in its efforts to become a global player in higher education. We recommend that both qualitative and quantitative studies be conducted by supervisors to explore and determine the overseas students’ motivation and learning behavior. We postulate development of an intellectual community that can stimulate challenges beyond the academic encounters. For both faculties, various forms of learning media for the promotion of effective communication should be developed and made available for flexible learning to occur. To help students improve their academic literacy, it is important ‘to identify the epistemological and ontological dimension for a flexible approach to learning’ (Tavakol & Dennick 2009). Formal counselling sessions can allow students to know what type of learner they are.